Análise de modelos de gestão da eficiência energética no transporte ferroviário Heavy Haul - RODRIGUES, Kardilson Pereira (2018)
ABSTRATC Freight transportation is strategic for any country seeking development, and the use of the rail modal is of relevance, especially in countries with continental dimensions. In the operation of a railroad, especially those classified as Heavy Haul, the management of energy efficiency is linked to both economic and environmental aspects, as these railroads use electric diesel locomotives, consuming a type of non-renewable energy (diesel), and with emission of ଶ. Over the decades, energy efficiency management practices in the world have evolved, especially in United States railroads, with more intense use of technologies and fleet renewal with more efficient locomotives. In Brazil, the few railroads have management models looking for this improvement, much in function of the higher costs of diesel, compared to railroads of other countries. Thus, an analysis of the energy efficiency management models of railroads of Brazil, the United States of America and Canada will be approached in order to propose a model for improving existing management processes and for new railway operations.